JUMPA Vol.3 No.3 Okt 2016 PENGARUH EARNING PER SHARE (EPS), DAN RETURN ON ASSETS (ROA) TERHADAP HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA: PENGARUH EARNING PER SHARE (EPS), DAN RETURN ON ASSETS (ROA) TERHADAP HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Irwan R Osman Sekolah Tinggi Ilmu Ekonomi YAI; Tegar Reza Pahlawan Sekolah Tinggi Ilmu Ekonomi YAI (Sekolah Tinggi Ilmu Ekonomi Y.A.I - Jakarta - Indonesia, 2016)
ROA) on stock prices on manufacturing companies listed on the Indonesia Stock Exchange in the period 2010 to 2014. The purpose of the research is to determine the effect of Earning Per Share (EPS) and Return On Assets (ROA) stock prices on manufacturing companies listed on the Indonesia Stock Exchange in the period 2009 to 2011. Variables used in the research is the independent variable consisting of Earning Per Share (EPS) and Return On Assets (ROA), and the dependent variable is the stock price. Research object is used by 13 companies of manufacturing companies listed in Indonesia Stock Exchange. Incoducting this research the methods used to test the hypotheses is multiple linear regression. Previously tested for statistic deskriptive, normality data and the assumption of classical test (test multicollinearity, heteroscedasticity, autocorrelation, normality regression) which shows that all variables used are free from multicollinearity, heteroscedasticity, autocorrelation, and all normally distributed variables using SPSS 21.00. The results in this research shows that these is significant effect of between the Earning Per Share (EPS) and Return On Assets (ROA) together on stock prices, and research result with the t test showed that the Earning Per Share (EPS) and Return On Assets (ROA) have a significant effect of on stock prices.